Takhrij and Syarah Hadith of Agrotechnology The Priority of Farming - Anisya Rizky Pradani; Wahyudin Darmalaksana; Budy Frasetya TQ (UIN Sunan Gunung Djati Bandung, 2021)
This study aims to discuss the hadith regarding the virtues of farming. This research method is a qualitative type through literature and field studies with the takhrij and sharah hadith approaches. The results and discussion of this research is that farming is a lawful job and is favored by Allah SWT which has many benefits for others or other living things. The conclusion of this study is the takhrij and syarah hadith of the Prophet about the virtue of farming which is almsgiving for a Muslim who grows plants and benefits his surroundings